Tajikistan on the move : statebuilding and societal transformations - Laruelle, Marlène (Contemporary Central Asia (Lanham, Md.), 2018)
This collection provides a broad and multidisciplinary examination of contemporary Tajikistan. The contributors analyze the political regime-its stability, legitimacy mechanisms, and patterns of centralization-as well as various aspects of its social fabric.